Monosomy 13q32.3----qter: report of two cases. Issue 2 (April 1985) - Rivera, H; González-Flores, S A; Rivas, F; Sánchez-Corona, J; Moller, M; Cantú, J M
Abstract : Two unrelated patients with monosomy 13q32.3----qter are reported. Comparison with six similar cases previously published indicates that the craniofacial dysmorphism of the 13qter monosomy syndrome is related to band 13q34, the thumb hypoplasia to band 13q32, and an apparently different phenotype to band 13q33. Coagulation deficiency appears to be non-specific in monosomy 13qter.